2022
DOI: 10.3389/fpubh.2022.1027514
|View full text |Cite
|
Sign up to set email alerts
|

At-home disposal practices of used insulin needles among patients with diabetes in China: A single-center, cross-sectional study

Abstract: BackgroundMost insulin injections for people with diabetes are administered at home, thus generating many used needles. Unsafe disposal of these at-home needles can lead to needle stick injuries, blood-borne disease transmission, and environmental contamination. Previous studies have shown varying results on the prevalence of and factors associated with safe sharps disposal practices of people with diabetes.ObjectiveTo assess the prevalence of and the factors associated with the safe disposal of used insulin n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Better understanding and mastery of pertinent information brought about by literacy in turn raises awareness of the significance of safe disposal, rectifies negative attitudes, and produces positive results ( 33 ). Some studies have shown that people with diabetes who possess awareness of the risk of transmission of bloodborne pathogens are more likely to take safety measures ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Better understanding and mastery of pertinent information brought about by literacy in turn raises awareness of the significance of safe disposal, rectifies negative attitudes, and produces positive results ( 33 ). Some studies have shown that people with diabetes who possess awareness of the risk of transmission of bloodborne pathogens are more likely to take safety measures ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…The medium-sized city of Jinzhou faces the same issue as the nation as a whole. Although a previous study was conducted in a southern Chinese city (23), the conclusions of this study are not necessarily applicable to the Jinzhou population due to the different economic, cultural and geographic contexts. Furthermore, in contrast to earlier research, this study uses the Knowledge, Attitude, Practice theoretical framework to thoroughly examine the influencing elements behind the region's present sharps disposal practices.…”
Section: Introductionmentioning
confidence: 88%
“…In 12 identified articles, there are 4155 patients with diabetes, as per Fig 1 . These articles were published between 2012 and 2022, with sample sizes ranging from 132 to 1436, and included eleven cross-sectional studies [5,10,[29][30][31][32][33][35][36][37][38], and one RCT studies [34]. One studies were conducted in Ethiopia [29], one in the Australia [30], two in the United States [5,31], one in Portugal [10], one in China [32], three in Malaysia [33][34][35], one in Pakistan [36], one in Saudi Arabia [37], and the other in Bosnia and Herzegovina [38]. Twelve studies reported the duration of diabetes in diabetes patients [5,10,[30][31][32][33][34][35][36][37][38], and ten reported the time of insulin injection [10,[29][30][32][33][34][35][36][37][38].…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…One studies were conducted in Ethiopia [29], one in the Australia [30], two in the United States [5,31], one in Portugal [10], one in China [32], three in Malaysia [33][34][35], one in Pakistan [36], one in Saudi Arabia [37], and the other in Bosnia and Herzegovina [38]. Twelve studies reported the duration of diabetes in diabetes patients [5,10,[30][31][32][33][34][35][36][37][38], and ten reported the time of insulin injection [10,[29][30][32][33][34][35][36][37][38]. The summary characteristics of these studies are shown in Table 2.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation